Information Frictions and Productivity Dispersion: The Role of Accounting Information - Hann, Rebecca N.; Kim, Heedong; Wang, Wenfeng; Zheng, Yue (The Accounting Review, 2020)
ABSTRACT Prior research documents large, persistent productivity dispersion even within narrowly defined industries, suggesting the presence of frictions that impede the efficient allocation of resources. In this paper, we consider the role of information frictions. We posit that high-quality financial reporting with respect to firm productivity can mitigate information frictions and hence facilitate the efficient allocation of resources across firms. Using a large sample of firms in the manufacturing sector, we find evidence consistent with our prediction—industries with higher productivity informativeness tend to have smaller within-industry productivity dispersion. We further find that this relation is stronger in industries with greater dependence on external financing, suggesting that reporting quality affects allocation efficiency, at least in part, through the capital market channel. These findings suggest that the extent to which financial reporting is informative about productivity can affect resource allocation efficiency and hence have real effects at the macro level.